KNOWLEDGE AND USE OF EMERGENCY CONTRACEPTIVES AMONG OUT-OF-SCHOOL FEMALE YOUTHS IN IDO LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2013)
Unintended pregnancy among youths resulting from unprotected sexual activities poses a major challenge to their reproductive health. Use of Emergency Contraceptive Pills (ECPs) which are of different brands has been identified to prevent unintended pregnancy. Studies have been carried out on the utilization and effectiveness of ECPs among older women but information on young women’s knowledge and its use will be useful in identifying gaps in knowledge and planning appropriate interventions. This study was therefore designed to assess the knowledge and use of ECPs among out-of-school female youths in Ido Local Government Area (LGA), Ibadan, Oyo State, Nigeria. The study was a cross-sectional survey involving a four-stage sampling technique. Four wards in the LGA and three villages from each ward were randomly selected. Four hundred female youths aged 15-24 years were identified and 377 who consented were interviewed using pre-tested semi-structured questionnaires. The respondents were apprentices, traders and farmers. Data on demography, reproductive and sexual health as well as practice of ECPs were collected. In addition, knowledge was assessed on an 18-point score with scores of <10 and ≥10 points considered to be poor and good knowledge respectively. Data were analyzed using descriptive statistics and Chi square at p= 0.05. Mean age of respondents was 20.7±1.1 years, 32.4% and 67.6% respondents were aged 15-19 and 20-24 years old respectively and 37.9% were married. Two hundred and sixty eight respondents (71.1%) were sexually active and 266 (70.6%) had been pregnant at least once. Two hundred and ten (78.9%) of the pregnancies were desired and 56 (21.1%) were unintended. Of the respondents who had unintended pregnancies, eight (14.3%) used ECPs once in three months and 40 (64.5%) had the pregnancies terminated with the consent of their partners. Two hundred and forty six (65.3%) of the respondents had ever heard of ECPs and 107 (28.4%) of them reported friends as source of information. The mean knowledge score on ECP was 11.1±2.0. Two hundred and sixty eight (71.0%) and 109 (28.9%) respondents had good and poor knowledge respectively. One hundred and ninety six (52.0%) respondents were aware of how ECPs work, while 144 (38.2%) knew how to take the drugs correctly. One hundred and thirty six (36.1%) respondents had ever used ECPs while 90 (24.0%) were current users and were mostly in the age group between 15-19 years old. Of the current users, 46 (51.1%) respondents used ECPs more than once in a month and 44 (49.0%) wished to continue their use. Age, accessibility and affordability were the factors that significantly affected the use of ECPs. Knowledge on emergency contraceptives was above average among out-of-school female youths. However, correct use and intention to continue its use was poor. Community based health education and peer education strategies should be instituted to improve knowledge and uptake of emergency contraceptives.